Ultrasonic inspection of grouted splice sleeves in precast concrete structures using elastic reverse time migration method. (1st February 2021) - Liu, Hai; Qi, Yuan; Chen, Zhijie; Tong, Huawei; Liu, Chao; Zhuang, Mingwei
Highlights: An ultrasonic imaging method is proposed for inspection of grouted splice sleeves. High imaging accuracy and resolution achieved by elastic reverse time migration. Numerical and laboratory experiments are conducted for the method validation. Grout defects inside the buried sleeve can are clearly imaged and identified. Abstract: Precast concrete (PC) structure has been widely employed for building construction in recent years, and grouted splice sleeve is commonly used for component connection. The compactness of the grouted splice sleeve connections plays a decisive role in structural safety, especially for its capacity to resist an earthquake. In this study, an ultrasonic imaging method is proposed for inspecting the grouted splice sleeves in PC structures using reverse time migration (RTM) algorithm based on an elastic wave equation. Numerical and laboratory experiments are carried out to assess the feasibility of our proposed method. In the numerical experiment, three numerical models, i.e. three-quarter grouted, fully-grouted, and non-grouted, are established. The results show that the proposed RTM method can reconstruct images of the buried sleeves with a higher resolution and a greatly-improved accuracy, compared with the traditional ultrasonic imaging method. Moreover, the grouting condition in the three models can be readily distinguished and even the interface between the grouting material and the air defect in the three-quarter grouted model can be clearly identified. In the laboratory experiment, two sleeves, one is fully-grouted and the other one is insufficiently-grouted with certain air defects, are embedded in a concrete model. The top of the two sleeves can be clearly imaged, and the insufficiently-grouted sleeve has a reflection, which is about 9 dB stronger than the other one. We conclude that the proposed ultrasonic imaging method can be used for inspecting the grouting quality of splice sleeves in PC constructions in field.